Hepatitis C virus genotype testing in paraffin wax embedded liver biopsies for specimen identification. Issue 12 (25th November 2003) - Ikura, Y; Ohsawa, M; Hai, E; Jomura, H; Ueda, M
Abstract : Despite advances in medical technology, careful specimen identification is still a fundamental principle of laboratory testing. If pathological samples are mixed up, especially in the case of extremely small biopsy samples, large amounts of time and energy may be wasted in correctly identifying the specimens. Recently, two liver biopsy specimens were mixed up in this department, and a new pathological technology was used to resolve the issue. Liver biopsy was performed on two patients with hepatitis C virus (HCV) infection. During sample transfer or tissue processing, the biopsy specimens were mixed up. Because the ABO blood group of the two patients was identical (type AB), the specimens were subsequently identified by analysing the HCV genotypes. RNA extracted from the paraffin wax embedded liver specimens was examined by a polymerase chain reaction based HCV genotype assay. This enabled the correct identification of the specimens, and each patient received the appropriate treatment on the basis of the accurate diagnosis.